Developing and Validating an EFL Teacher Imposed Identity Inventory: A Mixed Methods Study - Azra Gholamshahi; Minoo Alemi; Zia Tajeddin (Journal of Modern Research in English Language Studies)
Teacher-others relationship is one of the main features of teacher identity. As an aspect of this relationship, in some educational contexts, teachers experience imposition in their work place. As there is no survey tool to measure imposed identity, the present study developed a questionnaire based on the relevant literature and interviews with 44 EFL teachers, resulting in a 45-item questionnaire which was disseminated among 450 EFL teachers. An exploratory factor analysis of responses of EFL teachers yielded eight factors, namely: (1) Instructional, assessment, and interpersonal expectations imposed by managers and Supervisors, (2) Teacher professional responsibilities expected by stakeholders in the institute and the family, (3) Restrictions imposed on classroom discussion topics, dress code, and new technologies, (4) Suitability of teaching profession as perceived by the family, (5) Teacher responsibilities as expected by learners’ parents, (6) Gender stereotypes imposed by colleagues and the institute, (7) Learners’ and their parents’ instructional expectations, and (8) Observational and gender perceptions imposed by supervisors and managers. This study revealed the multi-dimensional nature of imposition in relation to which elements of identity change and harmonize under the influence of individual, contextual, and socio-cultural forces. The results of the study suggest that this scale is a reliable and valid measure of EFL teacher imposed identity. The findings can help researchers understand in what ways identity may be imposed and how it may change. Supervisors, institute managers, EFL teachers, and stakeholders can find the results of this study beneficial considering the fact that identity shaped and reshaped will certainly lead to a better EFL context for teaching and learning a foreign language.